Budidaya Lebah Trigona sp di Batang Kayu Pondok Pesantren Jabal Uhud : Pengabdian - Didik Suryamiharja S. Mabui; Ahmad Rifai Rahawarin; Liani Sari; Suwito; Andi Annisa Nurlia Mamonto; Irsan; Samuel Mamonto (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Bees are insect that can produce honey from nectar, pollen and resin collected by worker bees. Honey bees consist of 2 types, namely stinging and stingless bees known as klanceng or kelulut wasps. Both stinging and stingless bees are widely cultivated by the community. The honey produced by these two types of bees has different characteristics. Honey from stingless bees tends to be more liquid than honey produced from stinging bees which has a thick texture. This Community Service Activity was carried out at the Jabal Uhud Islamic Boarding School, Barru Regency, South Sulawesi, with the aim of increasing public insight and knowledge about trigonal bee cultivation to make it easier for the surrounding community. The technique of cultivating Trigonal bees in logs starts from making a bee house from used wood, modifying the shape of the box and making the size shape, moving the trigonal bees into the bee house, then the log is closed and ready to be placed in a predetermined place.